Effect of rituximab or tumour necrosis factor inhibitors on lung infection and survival in rheumatoid arthritis-associated bronchiectasis. (17th February 2020) - Md Yusof, Md Yuzaiful; Iqbal, Kundan; Darby, Michael; Lettieri, Giovanni; Vital, Edward M; Beirne, Paul; Dass, Shouvik; Emery, Paul; Kelly, Clive
Abstract: Objective: To evaluate rituximab (RTX) in patients with RA-associated bronchiectasis (RA-BR) and compare 5-year respiratory survival between those treated with RTX and TNF inhibitors (TNFi). Methods: A retrospective observational cohort study of RA-BR in RTX or TNFi-treated RA patients from two UK centres over 10 years. BR was assessed using number of infective exacerbation/year. Respiratory survival was measured from therapy initiation to discontinuation either due to lung exacerbation or lung-related deaths. Results: Of 800 RTX-treated RA patients, 68 had RA-BR (prevalence 8.5%). Post-RTX, new BR was diagnosed in 3/735 patients (incidence 0.4%). At 12 months post-Cycle 1 RTX, 21/68 (31%) patients had fewer exacerbations than the year pre-RTX, 36/68 (53%) remained stable and 11/68 (16%) had increased exacerbations. The rates of exacerbation improved after Cycle 2 and stabilized up to 5 cycles. Of patients who received ≥2 RTX cycles ( n = 60), increased exacerbations occurred in 7/60 (12%) and were associated with low IgG, aspergillosis and concurrent alpha-1-antitrypsin deficiency. Overall, 8/68 (11.8%) patients discontinued RTX while 15/46 (32.6%) discontinued TNFi due to respiratory causes. The adjusted 5-year respiratory survival was better in RTX-treated compared with TNFi-treated RA-BR patients; HR 0.40 (95% CI 0.17, 0.96); P =0.041. Conclusion: The majority of RTX-treated RA-BR patients had stable/improved pulmonary symptoms in this long-term follow-up. In isolated cases, worsening of exacerbation had definable causes. Rates of discontinuation due to adverse lung outcomes were better for RTX than a matched TNFi cohort. RTX is an acceptable therapeutic choice for RA-BR if a biologic is needed.